Developing kindergarten teacher capacity for play-based learning curriculum: a mediation analysis. (4th July 2022) - Cheung, Alan; Keung, Chrysa; Tam, Winnie
ABSTRACT: This study explores kindergarten teachers' beliefs about and practices of play-based learning with a focus on the mediation of teachers' capacity building with designing a play curriculum. Quantitative data are collected through a questionnaire with three cohort samples of 90 kindergartens who participated in a university-school partnership project. The data drawn from the first and second cohort years of 50 kindergartens are examined by Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) to ensure reliability and validity of the constructs. The third cohort year data from 40 kindergartens are used for examining the mediation effect. Results reveal that teacher beliefs are significantly associated with their pedagogical practices of play-based learning and their perceptions of whole-child development. Capacity building of teachers to practice a play-based learning curriculum partially mediates these associations and exhibits a strong association. Such capacities refer to teachers being able to design and adjust a play-based learning curriculum based on school background and developmental needs of children. Findings have significant practical implications for teacher education and professional development by strengthening relevant capacities.